Partial deligandation activated ZIF-67 for efficient electrocatalytic oxygen reduction reaction - Yang, Xiaoli; Gu, Jiali; Liu, Chenhong; Bai, Zhengyu; Yang, Lin (Frontiers in Chemistry, 2022)
Removing the blocked molecular groups and fully exposing the intrinsic active sites of metal-organic frameworks (MOFs) could give full play to their advantages of multi-active sites and multi-channel mass transfer, which will benefit the electrocatalytic oxygen reduction reaction (ORR) in fuel cells. Here, the partial diligandation-activated ZIF-67 (named as ZIF-67–400) with excellent ORR performance was obtained by simple low-temperature pyrolysis. The ORR electrocatalytic activity exhibits a half-wave potential of 0.82 V and the stability of maintaining 96% activity after 10 h of operation, which is comparable to commercial Pt/C. Further research studies reveal that the morphology, special dodecahedron configuration, and crystal structure of ZIF-67-400 are maintained well during the pyrolysis, but some hydrocarbon groups in the ligands are eliminated, resulting in the active sites being exposed and coordinated with the intrinsic porosity, improving the catalytic performance. This work may provide an alternative path for activating the electrocatalytic performance of metal-organic frameworks by low-temperature annealing.